The biopsy of the sentinel lymph node in multicentric breast carcinoma. Our experience - Palmieri, Renato; Lazzara, Salvatore; Sofia, Lorenzo; Calbo, Enrico; Racchiusa, Sergio; Calbo, Letterio (European Journal of Oncology and Environmental Health, 2009)
The biopsy of the sentinel lymph node (SLN) was considered an unreliable method in multicentric breast carcinomas. The Authors, revising old theories of the lymphatic drainage of the breast, demonstrate that the lymphatic outflow, following the ductal system, converges in the subareolar plexus and, from here, to the axillary lymphatic chain. Thus, the concept of “SLN of the breast” and not “SLN of the tumor” was born. These anatomical premises represent the rational of our study, that is to estimate the feasibility and the accuracy of the SLN biopsy after subareolar injection of radioactive tracer and vital dye in patients affected by multicentric carcinoma of the breast. From November 2005 to November 2008, 11 patients with multicentric carcinomas underwent the identification of sentinel lymph node by subareolar injection of radioactive tracer, surgical biopsy and total axillary lympho-adenectomy. This technique, although the limited number of cases, demonstrated a high degree of identification of SLN and a low incidence of false-negative cases. In conclusion, from our study it emerges that the axillary sentinel lymph node is representative of the entire mammary gland, the multicentric breast cancer would not any more be considered an absolute contraindication, and the subareolar injection of tracing could be the best technical option.